Domination of the Presence of Modern Retail Businesses over Traditional Retail Businesses in Perspective - Raden Roro Annisa Nur Salsabila; Balqis Farid; Muhibban (Values: Jurnal Kajian Islam Multidisiplin, 2025)
This research is based on the phenomenon of the dominance of modern retail businesses which are increasingly displacing the existence of traditional retail businesses in society, especially in the context of sharia economic law. The aim of this research is to analyze the impact of modern retail dominance on the sustainability of traditional retail businesses and its implications from a sharia economic law perspective. The method used is a qualitative approach with case studies in several retail business locations, involving in-depth interviews with business owners and analysis of documents related to sharia economic law. The research results show that although modern retail offers various conveniences and accessibility, traditional retail businesses still have important social and cultural values, but are threatened by business practices that are not in accordance with sharia principles. In general, the presence of modern retail does not conflict with sharia economic law as long as; Competition is carried out fairly and healthily, there are no unfair practices, monopoly or exploitation, and there is attention to economic balance and the welfare of small communities. The conclusions of this research emphasize the need for stricter regulations to protect traditional retail businesses and encourage business practices that are in accordance with sharia values, so that both types of businesses can operate harmoniously in a just economic ecosystem.